2012
DOI: 10.1007/s00221-012-3060-5
|View full text |Cite
|
Sign up to set email alerts
|

Impaired savings despite intact initial learning of motor adaptation in Parkinson’s disease

Abstract: In motor adaptation, the occurrence of savings (faster relearning of a previously learned motor adaptation task) has been explained in terms of operant reinforcement learning (Huang et al. in Neuron 70(4):787-801, 2011), which is thought to associate an adapted motor command with outcome success during repeated execution of the adapted movement. There is some evidence for deficient savings in Parkinson's Disease (PD), which might result from deficient operant reinforcement processes. However, this evidence is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 35 publications
(53 reference statements)
4
64
1
Order By: Relevance
“…These findings are in contrast to previous studies of various upper extremity visuomotor tasks which demonstrated significant involvement of the basal ganglia in savings of adapted movements [24,27,32]. We suggest that these differences potentially result from the differing nature and demands of adaptive locomotor and visuomotor tasks and perhaps the varying degree of overlearning allowed.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings are in contrast to previous studies of various upper extremity visuomotor tasks which demonstrated significant involvement of the basal ganglia in savings of adapted movements [24,27,32]. We suggest that these differences potentially result from the differing nature and demands of adaptive locomotor and visuomotor tasks and perhaps the varying degree of overlearning allowed.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies of visuomotor adaptation in PD have either minimized overlearning [32] or truncated the adaptation task such that asymptote was not attained [24]. To our knowledge, only Leow and colleagues [27] intentionally allowed for overlearning, but even then appeared to allow for only 10–15 trials of practice once the performance asymptote was reached. Indeed, previous research has noted impairments in PD when retaining newly-learned motor tasks in the absence of sufficient practice [28].…”
Section: Discussionmentioning
confidence: 99%
“…The conflicting outcomes may be explained by the fact that participants were able to see their own hand movements in the study of Teulings et al (2002). The results of Contreras-Vidal et al (2002) are in line with a recent study using an adaptation task in PD (Leow et al, 2012). In this study, participants moved a cursor from a start circle to a target circle on a digitizing tablet.…”
Section: Relearning Of Writing Skills In Parkinson's Diseasesupporting
confidence: 83%
“…The previously described problems with reinforcement learning in PD could thus explain the deficiently retained adaptation in PD. The study of Leow et al (2012) did not show an absolute deficit in reinforcement learning in PD patients. This suggests that continued repetition by PD patients could be associated with the outcome of success in the long run.…”
Section: Relearning Of Writing Skills In Parkinson's Diseasementioning
confidence: 59%
“…Such a reward prediction error could be used either to build the model-free motor memory through reinforcement learning (Darshan et al 2014;Izawa and Shadmehr 2011;Madelain et al 2011) independently of the adaptation of an internal model (Izawa et al 2012) or to tag the model-free motor memory in order to facilitate its recall when another reward prediction error is experienced (Shmuelof et al 2012). The involvement of reward prediction would also be consistent with the absence of savings observed in Parkinson's disease patients (Bédard and Sanes 2011;Leow et al 2012Leow et al , 2013Marinelli et al 2009). …”
Section: Discussionmentioning
confidence: 85%